Self-Enhancement, Conservation Values, and Personal Taxation Culture: How Education Level Moderates Their Relationship - Indrati, Menik; Prasetyo, Wisnu Budi; Purwaningsih, Eny; Faaroek, Safiani (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
This research investigates the influence of Self-Enhancement and Conservation on personal tax culture, by considering education level as a moderating factor. Involving employees at the Ministry of Law and Human Rights in West Java as research subjects, this research aims to understand how the encouragement to increase a positive view of oneself Self-Enhancement and conservation values (Conservation) contributes to the formation of attitudes and behaviour regarding tax obligations. The respondents in this research were 230 employees at the Ministry of Law and Human Rights in West Java. Data analysis uses Moderated Regression Analysis (MRA).. The research results show that Self- Enhancement and Conservation have a positive influence on personal tax culture. Furthermore, education level was identified as a significant moderator, able to strengthen the relationship between these factors and personal tax culture. Managerial implications involve developing strategies that combine Self-Enhancement and Conservation in training and tax policy, with tailored adjustments to individual financial conditions, to build a sustainable tax culture in the organization. Abstrak Penelitian ini menginvestigasi pengaruh Self-Enhancement dan Conservation terhadap budaya pajak pribadi, dengan mempertimbangkan tingkat pendidikan sebagai faktor moderasi. Melibatkan karyawan di Kementerian Hukum dan HAM di Jawa Barat sebagai subjek penelitian, penelitian ini bertujuan untuk memahami bagaimana dorongan untuk meningkatkan pandangan positif terhadap diri sendiri (Self-Enhancement) dan Conservation berkontribusi pada pembentukan sikap dan perilaku terkait kewajiban pajak. Responden pada penelitian ini sebanyak 230 karyawan di Kementerian Hukum dan HAM di Jawa Barat. Analisa data menggunakan Moderated Regression Analysis (MRA). Hasil penelitian menunjukkan bahwa Self-Enhancement dan Conservation memiliki pengaruh positif terhadap budaya pajak pribadi. Selanjutnya, tingkat pendidikan diidentifikasi sebagai moderator yang signifikan, mampu memperkuat hubungan antara faktor-faktor tersebut dan budaya pajak pribadi. Implikasi manajerial melibatkan pengembangan strategi yang memadukan Self-Enhancement dan Conservation dalam pelatihan dan kebijakan pajak, dengan penyesuaian yang disesuaikan dengan kondisi finansial individu, untuk membangun budaya pajak yang berkelanjutan di organisasi.